1979
DOI: 10.1007/bf00894045
|View full text |Cite
|
Sign up to set email alerts
|

Social‐ecological assessment of environments: Toward a two‐factor model

Abstract: A study was conducted to test the usefulness of the two-factor model in assessing social environments. Subjects were residents and staff at a residential treatment center for emotionally disturbed and/or delinquent boys and girls. Rating instruments consisted of (a) two parallel versions of Moos' Community-Oriented Programs Enivronment Scale (COPES), each worded so as to be appropriate to the setting being measured, and (b) global ratings of satisfaction with the environment. Principal component factor analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…Such a pattern of findings roughly parallels results reported by Kohn et al (1979), Fisher (1977, and Manderscheid, Koenig, and Silbergeld (1977). Results of factor analyses of Moos's Community-Oriented Program Environment Scales were reported in the first two of these three studies and factor analysis of the Classroom Environment Scale was reported in the third.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Such a pattern of findings roughly parallels results reported by Kohn et al (1979), Fisher (1977, and Manderscheid, Koenig, and Silbergeld (1977). Results of factor analyses of Moos's Community-Oriented Program Environment Scales were reported in the first two of these three studies and factor analysis of the Classroom Environment Scale was reported in the third.…”
supporting
confidence: 86%
“…Results of factor analyses of Moos's Community-Oriented Program Environment Scales were reported in the first two of these three studies and factor analysis of the Classroom Environment Scale was reported in the third. In the Kohn et al (1979) study support was found for a two-factor model of social environment. The two factors showed strong similarity both to Moos's Relationship and System Maintenance/System Change domains and our Factors I and II, respectively.…”
mentioning
confidence: 79%